Different Effects of Aspirin, Dipyridamole and UD-CG 115 on Platelet Activation in a Model of Vascular Injury: Studies with Extracellular Matrix Covered with Endothelial Cells - Eldor, A; Vlodavsky, I; Fuks, Z; Muller, T H; Eisert, W G (Thrombosis and Haemostasis, 1986)
Cultured endothelial cells produce an extracellular matrix (ECM) which activates platelets, similarly to deendothelialized vascular segments. Platelet-rich plasma (PRP) was incubated with endothelial cells cultures seeded in various densities on ECM. The interaction of the platelets with this artifical intima was evaluated by phase microscopy and by thromboxane A2 (TXA2) and prostacyclin (PGI2) measurement. Large platelet aggregates were formed on exposed ECM. Platelets aggregation but not adhesion on the ECM was markedly inhibited by the presence of endothelial cells. Pretreatment of the endothelial cells with 0.1 mM aspirin reduced their PGI2 synthesis and was associated with platelet aggregation on the ECM. 10 μM dipyridamole markedly inhibited platelet activation by ECM when the drug was added to citrated whole blood before PRP preparation. UD-CG 115 which elevates cyclic AMP in cardiac muscle, inhibited platelet aggregation and TXA2 production induced by ECM, in the presence as well as in the absence of endothelial cells, without any effect on endothelial PGI2 production.
Keywords: Extracellular matrix; Endothelial cells; Platelets; Prostacyclin; Thromboxane A2